Zrozumienie korupcji, jej przyczyn i skutków w ujęciu ekonomicznym - Zawojska, Aldona (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2003)
The paper reviews the essential elements of the variety of recent academic research on the concept, consequences and causes of corruption. It focuses on corruption as a problem that mainly arises in the interaction between government and the market economy. The paper includes study on the relationship between corruption and such variables as institutional quality, competition, government involvement, poverty and cultural determinants. Author concludes that corruption commonly goes along with policy distortions, inequality of income and lack of competition. Media freedom and the independence of the judiciary appeared to be essential factors in reducing the phenomenon. The study conclusion is that economic and political competition, government transparency and accountability are necessary instruments to restrict corruption.